The Risk Factors, Incidence and Prognosis of Postpartum Breast Cancer: A Nationwide Study by the SMARTSHIP Group - Park, Sungmin; Lee, Ji Sung; Yoon, Jae Sun; Kim, Nam Hyoung; Park, Seho; Youn, Hyun Jo; Lee, Jong Won; Lee, Jung Eun; Lee, Jihyoun; Hur, Ho; Jeong, Joon; Kim, Kweon-Cheon; et al. (Frontiers in Oncology, 2022)
The term 'pregnancy-associated breast cancer' is no longer used as it has been consistently reported that breast cancer during pregnancy and breast cancer after delivery (postpartum breast cancer) have different characteristics and prognosis. The purpose of this study is to define postpartum breast cancer by analyzing the incidence rate, related factors, and prognosis according to the timing of breast cancer. Data from the Korean National Health Insurance Service were used to analyze 1,292,727 women aged 20-49 years who birthed their first child between 2007 and 2012. The annual incidence rate of breast cancer after delivery increased every year (7.7 per 10,000 person-years after 5 years, 19.36 per 10,000 person-years after 10 years). The risk of breast cancer was significantly higher (hazard ratio 1.15, 95% CI 1.05-1.27, P=0.0037) in women diagnosed with gestational diabetes, but that was not associated with overall survival (OS). Patients diagnosed with breast cancer within 5 years of delivery had a poorer prognosis than those diagnosed later (5-year OS, <5 years: 91.1% vs. 5-10 years: 96.0%). In multivariate analysis of OS, the hazard ratio of patients diagnosed within 5 years after delivery was twice as high as of patients diagnosed between 5 and 10 years. Women diagnosed with gestational diabetes had an increased risk of breast cancer. Breast cancer patients diagnosed within 5 years of delivery had a poorer prognosis than those diagnosed later. In this regard, careful screening for early diagnosis of high-risk patients and intensive research on new treatment strategies are needed.